PENGARUH STRATEGI POSITIONING TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK AIR MINUM DALAM KEMASAN BOTOL MEREK NARMADA (STUDI KASUS : PADA MASYARAKAT LINGKUNGAN KEBUN SARI MATARAM) - Phyta Rahima (Jurnal Varian, 2018)
This study aims to examine the influence of positioning strategy variables consisting of Product Attributes, Product Benefits, Product Users, Product Competitors, and Product Benefits. Objects in this Research is Environmental Society Kebon Sari Ampenan Mataram City. The population of this research is all society environment Kebon Sari Mataram which consume drinking water in packing either gallon or bottle even glass. The sample in this study amounted to 30 people. Sampling using Nonprobability Sampling is by Purposive Sampling. The instrument of data collection using questionnaires with Likert scale which each have been tested and has fulfilled the validity and reliability requirements. Data analysis using multiple linear regression. The result of multiple linear regression analysis showed that product attribute had positive effect on purchasing decision with regression coefficient value from product attribute (X1) was 0,038 (positive value) with significance equal to 0,844 (<0,05). Benefit positive effect on purchasing decision with the value of regression coefficient from Benefit (X2) is 0,192 (positive value) with significance equal to 0,487. Users positively influence purchasing decision with value of regression coefficient of quality variable (X3) is 0,449 (positive value) with significance equal to 0,090. Competitor positively influence to purchase decision with value of regression coefficient from competitor (X4) is 0,048 (positive value) with significance equal to 0,073 (<0,05). The price of the product has a positive effect on the purchase decision with the coefficient value of 0.358 with the significance level of 0.073 (<0.05). From these results can be known that the biggest variables affect the purchase decision is the User.